Antarctica Contributions to Global Earth Sciences - Fütterer, Dieter K.; Fütterer, Dieter K.; Damaske, Detlef.; Damaske, Detlef.; Kleinschmidt, Georg.; Kleinschmidt, Georg.; Miller, Hubert.; Miller, Hubert.; Tessensohn, Franz.; Tessensohn, Franz. (Springer Berlin Heidelberg : Imprint: Springer, 2006)
Sixty articles arranged in eight thematic sections refer to most recent geological and geophysical results of Antarctic research. The Precambrian of the East Antarctic shield and its geological history is considered as well as sub-ice topography, geophysics and stratigraphy, sedimentology and geophysics of the surrounding Southern Ocean. Particular emphasis is given to the connection of the Antarctic and the surrounding continents when forming part of Gondwana.